Insulin-like growth factor-1 on cycle day 2 and assisted reproductive techniques outcome: A cross-sectional study - Fariba Abbasi; Robab Davar; Farimah Shamsi; Saeideh Dashti (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Individualized assisted reproductive techniques (ART) can improve ART outcomes. Some studies suggested using insulin-like growth factor-1 (IGF-1) level on cycle day 2 for individualized ART. Objective: To investigate the relationship between serum levels of IGF-1 on day 2 of the cycle and ART outcomes. Materials and Methods: In this cross-sectional study, cycle day 2 serum levels of IGF-1 were measured in 175 women aged between 18-44 yr as candidates for in vitro fertilization or intracytoplasmic sperm injection. All participants received antagonist protocol, and the relationship between serum levels of IGF-1 and ART outcomes according to the number of oocytes were investigated; poor responders (oocytes < 5), normal responders (oocytes 5-15), and hyper responders (oocytes > 15). Results: Poor responders had higher serum level of IGF-1 when compared with normal and hyper-responders; however,this difference was not statistically significant (p = 0.41). The serum levels of IGF-1 in women with zero retrieved oocytes and those cycles that were canceled for the inappropriate ovarian response were not significantly different compared to other women in the group of poor responders. An inverse relationship was observed between the serum level of IGF-1 and anti-Mullerian hormone. Furthermore, no significant relationship between serum level of IGF-1 with age, body mass index, number of 2 pronucleus, and number of embryos was observed. Conclusion: According to our results, the serum levels of IGF-1 may not be able to predict ART outcomes. It seems necessary to conduct more studies with larger sample size.